2011
DOI: 10.1073/pnas.1100631108
|View full text |Cite
|
Sign up to set email alerts
|

Persistent predator–prey dynamics revealed by mass extinction

Abstract: Predator-prey interactions are thought by many researchers to define both modern ecosystems and past macroevolutionary events. In modern ecosystems, experimental removal or addition of taxa is often used to determine trophic relationships and predator identity. Both characteristics are notoriously difficult to infer in the fossil record, where evidence of predation is usually limited to damage from failed attacks, individual stomach contents, onesided escalation, or modern analogs. As a result, the role of pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
108
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 94 publications
(114 citation statements)
references
References 31 publications
5
108
1
Order By: Relevance
“…However, our data, as well as those for several other groups (13,37,38), indicate that such interactions can have consequences, directly or indirectly, at higher taxonomic levels. Most compelling are cases of increasing incidence of taxa with well-developed antipredatory defenses, and it has been suggested that taxa possessing such traits may be more prone to speciation (38).…”
Section: Discussionsupporting
confidence: 51%
“…However, our data, as well as those for several other groups (13,37,38), indicate that such interactions can have consequences, directly or indirectly, at higher taxonomic levels. Most compelling are cases of increasing incidence of taxa with well-developed antipredatory defenses, and it has been suggested that taxa possessing such traits may be more prone to speciation (38).…”
Section: Discussionsupporting
confidence: 51%
“…In many cases, changes in fish morphology and the appearance of new higher taxonomic groups mark major shifts in the nature of fish-benthos interactions 14,19,20 . However, on modern reefs, and in aquatic systems in general, herbivory and other biotic interactions are characterized by considerable complexity 16,21 .…”
mentioning
confidence: 99%
“…Therefore, this indirectly shows that top-down trophic controls (i.e., predation) could be an important factor in macroevolution and long-term changes in phenotype distributions (Stanley 2008, Sallan et al 2011, Voje et al 2015. In this way the association of the higher values of á with 4 th order highstands of the sea level is an indirect effect of higher diversities of potential consumers of leiospheres (in this case graptolites), with the high sea level conditions.…”
Section: C Bmentioning
confidence: 99%
“…An increase in the diversity and productivity of prey could occur during the aftermath of an extinction event when the prey experiences relief from the negative effects of predation (Solé et al 2010), but eventually the long-term diversification of predators during the recovery phase following extinction (Sallan et al 2011) or delayed dispersal after immediate rediversification will down-regulate the prey to the presumed equilibrium values. Therefore, this indirectly shows that top-down trophic controls (i.e., predation) could be an important factor in macroevolution and long-term changes in phenotype distributions (Stanley 2008, Sallan et al 2011, Voje et al 2015.…”
Section: C Bmentioning
confidence: 99%